Preliminary Study on Operating Parameters toward the Metastable Zone-Width of Carbamazepine Co-Crystal - Engku Nadia, Engku Mat Nasir; Fatinah, Ab Rahman; Syarifah, Abd Rahim; Raihana Z., Edros; Nornizar, Anuar (Informatics Publishing Limited, 2017)
Objectives: Metastable zone width (MSZW) is a crucial parameter in designing co-crystallization process in order to achieve required crystal habits. The effects of operating parameters toward metastable zone width of carbamazepine-saccharin (CBZ-SAC) co-crystal were studied in this research. Methods/Statistical Analysis: Crystallization study was conducted using cooling crystallization method which involves polythermal method. A 250 ml scale size-reactor was used to study the effects of operating parameters on metastable zone width of CBZ-SAC co-crystal which tested with various mol ratio of SAC/CBZ, concentration of CBZ, cooling and heating rates and stirring speeds. Differential scanning calorimetry (DSC), X-ray powder diffraction (XRPD) and optical microscopy were applied to characterize the CBZ-SAC co-crystals. Findings: The results show that MSZW decreases as the mol ratios of SAC/CBZ increases, whilst also decreases with CBZ concentrations, cooling rates and stirring speeds. Application/Improvements: Cooling crystallization process is extensively used in the manufacture of pharmaceutical drugs.